Malononitrile‐involved Michael addition polymerization: An efficient and facile route for cyano‐rich polyesters with programmable thermal and mechanical properties. Issue 9 (14th March 2021) - Yang, Xiaoxia; Xie, Hongyan; Xu, Zhiguang; Feng, Jiabing; Fu, Qiwei; Li, Haidong; Jia, Yongtang
Abstract: An efficient, atom‐economic, oxygen‐tolerant, and water‐tolerant strategy has been established to synthesize cyano‐rich polyesters. Four kinds of organic bases, 1, 1, 3, 3‐tetramethylguanidine (TMG), 4‐dimethylaminopyridine, triethylamine, and 1, 5, 7‐triazabicyclo[4.4.0]dec‐5‐ene (TBD) were explored for accelerating Michael addition polymerization of malononitrile and 1, 4‐butandiol diacrylate. TMG can promote the polymerization efficiently under mild conditions to quantitatively afford polyester with high‐molecular weight and moderate polydispersity. The comparison of the kinetic studies of TMG and TBD reveals that TMG shows better catalytic performance, while the catalysis of TBD brings about oligomers in spite of the higher efficiency at early age of the polymerization. Moreover, other diacrylate compounds could also be quantitatively polymerized to afford polyesters with high molecular weight. When dimethacrylate is chose as the monomer, the polymerization becomes sluggish. All the afforded polyesters display programmable thermal and mechanical properties that are closely related to their chemical structures. Abstract :